Covid-19 e ‘cuidado de si’: percepções de saúde dos docentes da educação básica - Mossmann, Rodrigo (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation aims to investigate and portray the diversity of perceptions about health - with an emphasis on physical health - teaching and school routines of teachers at a state school in the city of Novo Hamburgo (RS); based on their experiences of the Covid-19 pandemic. The pandemic reverberated in the most different routines and demands of teachers, and the question asked was, how did basic education teachers practice ‘care of self' in relation to their health, especially physical health? This is an empirical study with a quantitative and qualitative approach. In order to investigate in greater depth the challenges teachers face in the context of the Covid-19 pandemic and Emergency Remote Education (ERE), a questionnaire on teachers' perceptions of their health was used as a research method. Twenty-seven teachers were invited and agreed to take part in the survey. The results were analyzed and grouped into six categories of analysis: identification of employees, perception of physical health, perception of mental health, lifestyle, ‘care of self' and teaching health, based on the Covid-19 pandemic and teaching challenges in ERE. The perception of teachers' health was positive in the three contexts analyzed (before/during the Covid-19 pandemic and currently). The ‘care of self' in relation to health, on the other hand, was awakened in teachers, based on the discourses and practices associated with taking care of physical exercise, eating well, carrying out preventive health tests, improving sleep and reducing stress. The results of this study contribute both to the body of knowledge related to the subject in question and to the creation of strategies to promote and prevent teachers' health/quality of life.
Keywords: Pandemia da Covid-19; ‘Cuidado de si’; Saúde; Docentes; Covid-19 pandemic; ‘Care of self'; Health; Teachers; ACCNPQ::Ciências Humanas::Educação